Semaglutide, type 2 diabetes, and the risk of nonarteritic anterior ischemic optic neuropathy - Fernando K. Malerbi; Marcello C. Bertoluci (International Journal of Retina and Vitreous)
Abstract In the last months, conflicting evidence on a possible association between the use of semaglutide and incident nonarteritic anterior ischemic optic neuropathy (NAION) has emerged. A recently published study, which evaluated all patients with type 2 diabetes in Denmark, has shown with robustness that once-weekly semaglutide doubles the five-year risk of NAION. In this comment, the new evidence is discussed, along with practical implications for type 2 diabetes patients. The possibility of ophthalmological evaluation regarding optic disc morphology is suggested, before initiation of semaglutide treatment or, for those patients already under treatment, during a follow-up ophthalmological visit. If a disc-at-risk pattern is detected, such information could be brought to the attention of the attending clinician involved with diabetes control and discussed with patients for a shared decision-making approach. A new risk-benefit discussion weighing the undoubted benefits of semaglutide in reducing cardiovascular mortality and cardiovascular events, heart failure hospitalization, and renal protection must be started and carefully balanced against a rare but devastating condition such as NAION.